Integrated methodology for industrial facilities management and design based on FCA and lean manufacturing principles. Issue 7 (21st February 2020) - Guillen, Diego; Gomez, Diego; Hernandez, Ingrid; Charris, Daniela; Gonzalez, Juan; Leon, Daniel; Sanjuan, Marco
Abstract : Purpose: The purpose of this paper is to provide a comprehensive methodology and a case study about the successful integration of FCA with continuous improvement tools for strategic decision-making processes. Reliable knowledge of the condition of tangible assets and their ability to fulfill their target activities over time are required for an assertive strategical decision process. Facility condition assessment (FCA) is a recognized methodology that allows the systematic evaluation of this performance. For those companies whose primary objective is the production of goods, decisions associated with improvements on the productive system or re-adaptation of existing assets may also require the implementation of alternative methodologies, with a direct impact on the indicators of the company and therefore on the FCA. Design/methodology/approach: This study presents a methodology for the integration of FCA and lean manufacturing (LM) as a tool in strategic decision-making process that involves the integration of continuous improvement processes or significant changes in the production process, in which the condition of the installation impacts decisively the productivity of the system. Findings: The results of the implementation on an insecticide and herbicide production plant indicate an increase of 33 per cent in the capacity of the formulation process and over 20 per cent reduction in the internal quality claims associated with the packaging system. Practical implications: Those methodological stages are applicable to facilities in which the FCA shows the need for significant reconditioning of assets, the need to increase the efficiency and/or the production capacity. This methodology integrates elements of continuous improvement and redesign of production systems. Originality/value: The original value of this paper is oriented to the capacity to integrate different FCA and LM tools through the company indicators of productivity key performance indicators and, in addition, of a comprehensive illustration based on a study case.